2009
DOI: 10.1515/jgt.2008.068
|View full text |Cite
|
Sign up to set email alerts
|

Class-preserving automorphisms and the normalizer property for Blackburn groups

Abstract: Abstract. For a group G, let U be the group of units of the integral group ring ZG. The group G is said to have the normalizer property if N U ðGÞ ¼ ZðUÞG. It is shown that Blackburn groups have the normalizer property. These are the groups which have non-normal finite subgroups, with the intersection of all of them being non-trivial. Groups G for which classpreserving automorphisms are inner automorphisms, Out c ðGÞ ¼ 1, have the normalizer property. Recently, Herman and Li have shown that Out c ðGÞ ¼ 1 for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In particular, the normalizer property holds for finite groups of odd order. Other positive results on this problem can also be found in [4][5][6][7][8][9][10][11][12][13][14][15]. Denoted by Aut Z (G) the group consists of all the automorphisms of G inducing an inner automorphism of ZG.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, the normalizer property holds for finite groups of odd order. Other positive results on this problem can also be found in [4][5][6][7][8][9][10][11][12][13][14][15]. Denoted by Aut Z (G) the group consists of all the automorphisms of G inducing an inner automorphism of ZG.…”
Section: Introductionmentioning
confidence: 97%
“…The first results for p-groups, nilpotent groups and groups with normal Sylow 2-subgroups are due (respectively) to D. Coleman [2], A. Saksonov [21], S. Jackowski and Z. Marciniak [16]. Further work by, among others, S. Sehgal, M. Parmenter, Y. Li [1], E. Jespers and M. Hertweck [13], M. Hertweck [11,12,9] and M. Hertweck and W. Kimmerle [14] enlarged the class of groups with a positive answer greatly. M. Mazur [19,20] showed that the question is closely related to the Isomorphism problem.…”
Section: Introductionmentioning
confidence: 99%
“…Hertweck [2] constructed a group G of order 2 25 · 97 2 for which the normalizer property fails. For positive results on the normalizer problem, the reader may refer to [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. According to the Coleman's result ([7, Coleman Lemma]), the normalizer property holds for G provided that Out Col G = 1.…”
Section: Introductionmentioning
confidence: 99%